Testing differences in long run growth among Spanish regions: Can growth models explain it? - Julio Herrera Revuelta; Jesus Santamaria Fidalgo (European Regional Science Association (ERSA), 1998)
During the last decade we have assisted to a renewal interest in growth. There were a great number of theoretical and empirical works since the question was reopen by the Romer (1986) article about long run properties of growth models. Growth models can be classified in two kinds: exogenous growth models and endogenous growth models. The main differences between them are that the endogenous models try to incorporate into the behavior of the agents the assumptions that the first assumes as exogenous. This difference, that sounds only methodological, has important implications. The conclusion of the exogenous models is that, in presence of free factor mobility and free diffusion of technology, countries and regions will converge to the same rate of growth, and, in absence of technical progress, they will converge to the same level of per capita income, without any influence of initial conditions or political intervention in the economy (This result is obtained by Barro(1991) and Barro y Sala(1992)). With endogenous models the economies will growth at a rate determined by the behavior of the agents in the economy and could be the same or different among different economies. The theoretical result of these models is that in the long run could exist convergence or divergence. The main focus of this paper is, using the data for Spanish Regions from 1955 to 1991 and applying unit root time series methodology, to determine long run growth rates for each region with the aim of knowing if we can choose between the two kind of growth models.
Keywords: 330